Criterios fraternales para la implementación de políticas públicas en materia de seguridad ciudadana y para la reforma de las instituciones policiales - Barreneche, Osvaldo (2011)
This article deals with past and present police reforms. It argues that political control and policy making regarding law enforcement agencies are complex yet relevant issues that need to be studied and debated in both academic and public institutions. Fraternity, as a working concept, could be a useful tool for implementing new policies in orden to avoid previous mistakes and shortcomings of on-going reform processes.